The Effect of Price and Product Quality on Wardah Product Purchasing Decisions at Hasanah Mart Air Haji - Sindi Gufina Sari; Afriyeni Afriyeni (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine and analyze the effect of price and product quality on purchasing decisions (studies on Wardah cosmetic products at Hasanah Mart Air Haji). This is a quantitative study with multiple linear regression data analyses. The number of respondents was 91 people. The data was collected using a questionnaire. Based on the results, it can be stated that there is a negative and significant influence between price and purchase decisions. Then, there is a positive and significant influence between product quality and purchasing decisions. The variable that has the most influence on purchasing decisions is perceived price, so companies can maintain prices that are quite affordable and continue to make the latest innovations to improve purchasing decisions for Wardah cosmetic products.